The Relationship Between Avatar Identification Factors and Vicarious Pleasure: The Moderating Role of Affect Intensity in the Metaverse - Jaehyuk Choi; Youngkeun Choi (Journal of Metaverse)
This study investigated the connection between avatar identification factors, sharing intentions, and the influence of vicarious pleasure. Additionally, it explored the moderating effect of affect intensity on this relationship. For this, data was collected from 228 college students in South Korea through a survey. This study used hierarchical regression. The findings revealed several key points. Firstly, participants who perceived greater similarity identification, wishful identification, and embodied presence in their avatars within the metaverse platform reported higher satisfaction with their avatars. Secondly, participants who experienced a higher sense of embodied presence in their avatars were more inclined to share their avatars due to the vicarious pleasure they derived from it. Lastly, the positive correlation between perceived embodied presence and vicarious pleasure was stronger for participants with higher affect intensity in the metaverse platform. This study is the first to examine the integral model of avatar identification factors in the metaverse platform.